Correlating polyethylene microstructure to stress cracking: Development of primary structure parameters. (4th July 2018) - Fodor, Jeff S.; Lamborn, Mark J.; DesLauriers, Paul J.
Abstract: New primary structure parameters ( PSP3 and PSP3* ) were developed to help better understand the effects of polymer microstructure on polyethylene stress cracking as determined by post yield tensile tests. Previously, the structure parameter, PSP2, was obtained using only molecular weight distributions (MWD) and short chain branching distributions (SCBD) obtained from size exclusion chromatography coupled to a Fourier transform inferred detector (SEC-FTIR). By augmenting the MWD and SCBD with differential scanning colorimetry (DSC) analysis to better estimate crystalline lamella distributions, a more robust process was developed to estimate the critical lamella distance, L, that a molecule must span to form a tie molecule. Improvements were also made to estimate the end to end distance, R, by including SCB effects on persistence length, and consideration for the probability of more than one tie molecule per polymer chain was included in the calculation. By generating a three dimensional, digital, crystalline-lattice and using random walk statistics, PSP3 and PSP3* values were estimated for various monomodal and bimodal copolymers as well as homopolymer resin sets. Furthermore, a new parameter; the average number of crystalline lamella per polymer chain (ANCC) was developed. The entire method required low computational time, while allowing us to investigate very large molecular weights. These latter parameters ( PSP3* and ANCC) capture for the first-time, ties formed between multiple lamella by a single polymer chain. Good correlations between the strain hardening modulus (ISO, 18488 test standard) and PSP3* were found as well between ANCC −1 values and the % natural draw ratio (NDR) at 80 °C. Graphical abstract: Image 1 Highlights: New structure parameters were developed from data and random walk statistics. Parameters, PSP3* and ANCC adequately captured post yield tensile behavior. A wide variety of polyethylene architectures were successfully correlated. PSP3* and ANCC will be very useful tools to aid catalyst and resin design.